Physiological Implications of the Kinetics of Maize Leaf Phosphoenolpyruvate Carboxylase - Tovar-Méndez, Alejandro (American Society of Plant Physiologists, 2000)
It has been a common practice to assay phosphoenolpyruvate carboxylase (PEPC) under high, nonphysiological concentrations of Mg(2+) and bicarbonate. We have performed kinetic studies on the enzyme from maize (Zea mays) leaves at near physiological levels of free Mg(2+) (0.4 mm) and bicarbonate (0.1 mm), and found that both the nonphosphorylated and phosphorylated enzymes exhibited a high degree of cooperativity in the binding of phosphoenolpyruvate, a much lower affinity for this substrate and for activators, and a greater affinity for malate than at high concentrations of these ions. Inhibition of the phosphorylated enzyme by malate was overcome by glycine or alanine but not by glucose-6-phosphate, either in the absence or presence of high concentrations of glycerol, a compatible solute. Alanine caused significant activation at physiological concentrations, suggesting a pivotal role for this amino acid in regulating maize leaf PEPC activity. Our results showed that the maximum enzyme activity attainable in vivo would be less than 50% of that attainable in vitro under optimum conditions. Therefore, the high levels of PEPC protein in the cytosol of C(4) mesophyll cells might be an adaptation for sustaining the steady-state rate of flux through the photosynthetic CO(2) assimilation pathway despite the limitations imposed by the PEPC kinetic properties and the conditions of its environment.